Yang Huilin, China Christianity and the Question of Culture, Waco, Baylor University Press, 2014, 272 pp. - Martínez Esquivel, Ricardo (Estudios de Asia y África, 2016)
Yang Huilin, China Christianity and the Question of Culture, Waco, Baylor University Press, 2014, 272 pp.